2017
DOI: 10.1515/abcsb-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Tissue Cultures of Four Crocus Species from the Carpathian Basin

Abstract: We aimed to produce tissue cultures and plant regeneration from endangered Crocus species: C. scepusiensis, C. tommasinianus, C. vittatus ("Verni" series of the genus) and C. banaticus. For initiation of cultures we used a plant growth regulator (PGR) combination used for in vitro culture of saffron and its relatives: 10 mg L -1 α-naphthaleneacetic acid (NAA) and 1 mg L -1 6-benzyladenine (BA). Shoot tips of young seedlings (C. scepusiensis) and corms (for the rest of species) were used as explants. C. scepusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…After the cultures had been initiated, multiplication experiments were performed. It is usually reported that reduced NAA concentrations in comparison to BAP promote in vitro bulblet proliferation in geophytes (Hussey, 1982;Seabrook, 1990;Santos et al, 1998;Langen-Gerrits and de Klerk, 1999;Santos et al, 2002;Freytag et al, 2017;Juan-Vicedo et al, 2019;Rahimi Khonakdari et al, 2020), as revealed in this study. However, determination of the specific concentration of these PGRs in culture media is crucial for successful micropropagation of the target species (de Klerk, 2012;Freytag et al, 2017).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…After the cultures had been initiated, multiplication experiments were performed. It is usually reported that reduced NAA concentrations in comparison to BAP promote in vitro bulblet proliferation in geophytes (Hussey, 1982;Seabrook, 1990;Santos et al, 1998;Langen-Gerrits and de Klerk, 1999;Santos et al, 2002;Freytag et al, 2017;Juan-Vicedo et al, 2019;Rahimi Khonakdari et al, 2020), as revealed in this study. However, determination of the specific concentration of these PGRs in culture media is crucial for successful micropropagation of the target species (de Klerk, 2012;Freytag et al, 2017).…”
Section: Resultssupporting
confidence: 70%
“…It is usually reported that reduced NAA concentrations in comparison to BAP promote in vitro bulblet proliferation in geophytes (Hussey, 1982;Seabrook, 1990;Santos et al, 1998;Langen-Gerrits and de Klerk, 1999;Santos et al, 2002;Freytag et al, 2017;Juan-Vicedo et al, 2019;Rahimi Khonakdari et al, 2020), as revealed in this study. However, determination of the specific concentration of these PGRs in culture media is crucial for successful micropropagation of the target species (de Klerk, 2012;Freytag et al, 2017). Among the four combinations of PGRs used for multiplication in the present work, the best response was obtained in M3 (10 μM BAP + 5 μM NAA) that showed significantly higher bulblet induction in N. alcaracensis (4.35±0.59), N. eugeniae (5.95±0.60) and N. hedraeanthus (9.00±0.72).…”
Section: Resultssupporting
confidence: 70%
“…In the present study, the major aim was to develop a promising lowcost and easy-to-use recipe for disinfection of the Crocus corms as a crucial step of an in vitro propagation workflow, as well as a platform to better conservation of wild Crocus species and effective regeneration protocol towards gene and genome editing of Crocuses in future studies. Although a few studies reported bleach and ethanol as the only ingredients for the disinfection procedure (Freytag et al, 2017), according to our results, common surface sterilizers such as sodium hypochlorite and ethanol are not effective to control contamination of Crocus corms, particularly wild C. caspius and C. speciosus. The major problem with hypochlorites is their instability and sensibility to light (Connell 2006).…”
Section: Discussionmentioning
confidence: 57%
“…The present study demonstrated that the production of callus biomass with the use of solid media (Murashige and Skoog) added with a growth regulator 2,4-dichlorophenoxyacetic acid, BAP, and phenylalanine precursor increased the callus wet weight (Figure 2). This study is relevant to the previous study showing that the use of a BAP growth regulator in the same concentration successfully produced a callus [41]. The use of phenylalanine reportedly affects the formation of some secondary metabolites.…”
Section: Disscussionsupporting
confidence: 53%